Mortality from COV-19 Infections Among Health Care Workers Compared to the General Population - Afshan Sadiq, Faisal Rahman, Urooj Manzoor, Saifullah, Shehla Farhin, Muhammad Shoaib Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The primary goal of this study is to evaluate the rates of death from coronavirus infection among healthcare personnel against those in the general population. Study Design: Comparative study Place and Duration: This study was conducted at Benazir Bhutu Hospital Rawalpindi during the period from July, 2022 to September, 2022. Methods: 135 coronavirus-infected individuals of both genders were studied. Patients were aged 20–65 years. All patients gave written consent for baseline data on age, sex, body mass index, socioeconomic status, and domicile. Patients were symptomatic and asymptomatic. Among 135 cases, 65 were health workers in group I and 70 were general population in group II. Mortality among both groups were compared. ICU hospitalization, ventilation, and death were compared between groups. SPSS 22.0 analyzed all data. Results: There were 35 males in group I with mean age 26.13±10.72 years and in group II 40 were males with mean age 45.6±5.27 years. We found that number of died patients were higher in group II 9 (12.9%) as compared to group I 3 (4.6%). Older age, heart disease, diabetes mellitus and lack of personal protective equipment (PPE) were the most common reasons of died coronavirus patients. Conclusion: The results of this study indicate that older age, heart disease, and diabetes are independently associated with a higher risk of death and a greater severity of pandemic disease among the general public than they are among health care professionals. Keywords: General Population, Ventilation, Mortality, Coronavirus, Health workers,